Proyecto de inversión para la creación de una empresa productora y comercializadora de limpiavidrios de la Región Sur del Ecuador - Aldaz Pesantez, Epifanía Berónica (2016)
The National University of Loja, Career Business Administration Area Social and Administrative Law aims to train professionals with high academic and social spirit capable of contributing to the development of cities, provinces and regions. This research seeks to contribute to society in the southern region by giving its people a product that meets the needs not being met by the large multinationals, so that, for the development of this paper made some step among which are the introduction, literature review, materials and methods, results, discussion, conclusions, recommendations and the relevant literature. In the phase of results is all the same primary information that was provided by prospective clients or target population, while in the discussion is some studies such as: Market Research, the Technical, organizational and their respective financial evaluation using the five evaluation indicators. In market research we will find a detailed analysis of the demand that the same focus from the potential demand, real and effective, also conducted an analysis of supply data that was provided by the companies producing and marketing of cleaner. With this data could make a balance between demand and supply it allowed us to meet the unsatisfied demand is 397,995 liters of liquid glass cleaner. The technical study allowed the design installed capacity and the use giving us the first year the result of 388,800 units of 500cm ³ (half liter) in regard to the location of the plant will be located in the city of Loja on the streets Juan Salinas between Sucre and Bolivar and engineering of the project provided insights into the machinery and equipment that are to used in the production process. The organizational study allowed us to design first the legal structure of the company to later perform the same administrative organizational structure to tell the following 5 departments: Management, secretary, legal, production department and finance and driver, each of these departments’ defined functions that help them to good development or operation of the company. The financial study is structured with the same investment stage is divided into fixed assets amounting to a total of $ 39,019, deferred assets is $ 8600 and a working capital is $ 83664.4, and these values represent the initial investment is necessary for the business idea come into operation which makes a total of $ 83,664.40 will be funded the same as a 30% contribution of the partners and the remaining 70% with credit Finance Corporation. The retail price of the products is $ 1.35 in the first year and reached a maximum $ 1.56 in the fifth year. The annual production sales generate the same revenue amounting to $ 525,576.77 for the first year while for the fifth year is $ 604,752.25. The financial evaluation is a technique that measures the profitability of a project which was applied to indicators such as NPV, IRR, benefit-cost ratio, payback period and the sensitivity analysis, which yielded the following results: The result is net present value of $ 168,200.2 remain positive. The result of the internal rate of return is 68.59% higher than the opportunity cost. The cost benefit ratio is 1.77, greater than one. The capital recovery period is 1.62, which means that the investment will Reclaim in a year seven months and thirteen days. Sensitivity analysis allowed measuring the variations or fluctuations in the market, giving us the result that the project supports a 9% increase in costs, and an 8% decrease in revenue.